Platinum-group element signatures in the North Atlantic Igneous Province: Implications for mantle controls on metal budgets during continental breakup - Hughes, HSR; McDonald, I; Kerr, AC (Lithos, 2015)
This is the final version of the article. Available from the publisher via the DOI in this record. The North Atlantic Igneous Province (NAIP) is a large igneous province (LIP) that includes a series of lava suites erupted from the earliest manifestations of the (proto)-Icelandic plume, through continental rifting and ultimate ocean opening. The lavas of one of these sub-provinces, the British Palaeogene Igneous Province (BPIP), were some of the first lavas to be erupted in the NAIP and overlie a thick crustal basement and sedimentary succession with abundant S-rich mudrocks. We present the first platinum-group element (PGE) and Au analyses of BPIP flood basalts from the main lava fields of the Isle of Mull and Morvern and the Isle of Skye, in addition to a suite of shallow crustal dolerite volcanic plugs on Mull, and other minor lavas suites. BPIP lavas display both Ssaturated and S-undersaturated trends which, coupled with elevated PGE abundances (NMORB), suggest that the BPIP is one of the most prospective areas of the NAIP to host Ni–Cu–PGE–(Au) mineralisation in conduit systems. Platinum-group element, Au and chalcophile element abundances in lavas from West and East Greenland, and Iceland, are directly comparable to BPIP lavas, but the relative abundances of Pt and Pd vary systematically between lavas suites of different ages. The oldest lavas (BPIP and West Greenland) have a broadly chondritic Pt/Pd ratio (~1.9). Lavas from East Greenland have a lower Pt/Pd ratio (~0.8) and the youngest lavas from Iceland have the lowest Pt/Pd ratio of the NAIP (~0.4). Hence, Pt/Pd ratio of otherwise equivalent flood basalt lavas varies temporally across the NAIP and appears to be coincident with the changing geodynamic environment of the (proto)-Icelandic plume through time. We assess the possible causes for such systematic Pt/Pd variation in light of mantle plume and lithospheric controls, and suggest that this reflects a change in the availability of lithospheric mantle Pt-rich sulphides for entrainment in ascending ...